Effect of Thin Polymer Layers on Mechanical Properties of Metal Surfaces (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
: A study of the effect of epoxy-polyester powder coatings on the mechanical properties of plates made of rolled sheet steel has been carried out. The effect of a coating with a thickness of about 100 μm on the mechanical properties of samples with a thickness of 0.7-1.5 mm was considered. Tests carried out at room and elevated temperatures showed that thin coatings insignificantly affect the mechanical properties of plates in bending and tensile tests. In particular, the stiffness of the plates under tension and bending practically does not change in the presence of coatings, despite the fact that the modulus of elasticity determined in tests of steel plates with coatings is always slightly lower than the Young's modulus of steel, due to the increased thickness of the samples, determined taking into account the presence of coatings. In contrast, in compressive strength tests, the effect of coatings is significant. In the supercritical deformation mode, the bearing capacity of the coated plates is significantly reduced, and their critical buckling load is 1.2–2.3 times lower (depending on the substrate thickness) in comparison with uncoated specimens. This effect can be explained by the influence of residual temperature stresses arising in the samples after the deposition of coatings.